PENGARUH PEMANASAN BAHAN BAKAR MELALUI PIPA BERSIRIP TRANSVERSAL PADA UPPER TANK RADIATOR DAN PENAMBAHAN ETANOL TERHADAP EMISI GAS BUANG PADA TOYOTA KIJANG - Danar Susilo Wijayanto; Ngatou Rohman; Ranto Ranto; Husin Bugis; Ahmad Yuhsin Sukisno; Muhammad Rodhi Qoribi (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2014)
The purpose of this study were to determine the effect usage of gasoline heating through a capillarytube which is transversal finned in the upper tank of radiator on exhaust emissions of CO and HC in the engineof Toyota Kijang. This study is experimental. The sample in this study was the machine of Toyota Kijang. Freevariable of the research is the usage of fuel heating with fin variations on the copper capillar tube consist ofcopper capillar tube without fin, finned copper capillar tube with the ranges between the fins are 10 mm, 20 mm,and 30 mm and variations of ethanol in premium 0%, 5%, 10%, 15%, 20%, 25%, and 30%. Experimentalmethod to measure exhaust emissions of CO and HC in the engine of Toyota Kijang. The result of this researchshows that (1) The lowest carbonmonoxide gas emissions level was foundin the heating of copper pipe with 20mm fins distance in the solution of fuel and ethanol 30% at 0.209 (% vol). (2) The lowest Hydrocarbon emissionslevel was found in the heating of pipe with 10 mm fins distance in the solution of gasoline and ethanol 20% at294.33 (ppm vol). (3)The heating of copper pipe with 20 mm spacing between the fins and the variation ofethanol 30% is the best result of the entire treatments with CO gas at 0.209 (% vol) and HC at 310.00 (ppm vol).(4) The heating in fuel mixture gasoline 75% and ethanol 25% through radiator upper tank with gap betweenfins 10 mm is the best treatment than from other treatment in testing use with CO t 0,31 (%vol) dan HC at 340(ppm vol).